Magnetic Properties of Transition Metal Ion doped LiCuVO4 - Chatterjee, Sandip; Kumar, A.; Shahi, P.; Ghosh, A.K.; Nigam, A.K. (Asian Journal of Chemistry, 2011)
The magnetic properties of Mn- and Zn-doped LiCuVO4 were investigated. With Zn-doping the high temperature region remains antiferromagnetic but with Mn-doping it shows small ferromagnetic ordering. For both transition metal ions doping the intrachain exchange integral decreases. Zn-doping has very minor effect on LiCuVO4 and the long range ordering with very minute ferromagnetic moment has been observed whereas for Mn-doped sample long range ordering with appreciable ferromagnetic moment has been observed.